Material handling system for flexible manufacturing cell - Wong, Chiak Wu. (2008)
The objective of this project was to focus on implementing the elements of automated material handling system which are used to pack, label and transport finished products in a flexible manufacturing cell in a medical equipment manufacturing plant. Apart from reinforcing engineering knowledge and principles, this project provided the opportunity to study / analyses a real life challenge facing the implementation of Computer Integrated Manufacturing (CIM) system in a manufacturing environment.